The Effect Of Health Education Using E-Booklets On Medication Adherence In Type Ii Dm Patients - Sri Wahyuni (Al-Makki Publisher, 2024)
This study aims to evaluate the effect of health education using E-Booklet on adherence to taking medication in type II diabetes mellitus (DM) patients at the Internal Medicine Polyclinic of Mitra Kasih Hospital. This study describes the level of compliance with taking medication before and after the E-Booklet education intervention. The results showed that before education, the majority of patients (83.6%) had low compliance, while after education, the level of low compliance decreased to 61.8%. Statistical analysis showed a significant effect of E-Booklet education on drug compliance with a p value = 0.003 at a significance level of 0.05. This study contributes theoretically to the science of surgical medical nursing and practically for Mitra Kasih Hospital in improving health education about adherence to taking medication in DM patients.